Income Shocks and Adolescent Mental Health - Baird, Sarah; de Hoop, Jacobus; Ozler, Berk (2012)
In this paper, the authors investigate the effect of positive income shocks on the mental health of adolescent girls using experimental evidence from a cash transfer program in Malawi. They find that the provision of monthly cash transfers had a strong beneficial impact on the mental health of school-age girls during the two-year intervention. Among baseline schoolgirls who were offered unconditional cash transfers, the likelihood of suffering from psychological distress was 38 percent lower than the control group, while the same figure was 17 percent if the cash transfers offers were made conditional on regular school attendance. The authors find no impact on the mental health of girls who had already dropped out of school at baseline. The beneficial effects of cash transfers were limited to the intervention period and dissipated quickly after the program ended.